First intraindividual comparison of contrast-enhanced MRI, FET- and DOTATOC-PET in patients with intracranial meningiomas - Dittmar, Jan Oliver; Kratochwil, Clemens; Dittmar, Anne; Welzel, Thomas; Habermehl, Daniel; Rieken, Stefan; Giesel, Frederik L.; Haberkorn, Uwe; Debus, Jürgen; Combs, Stephanie (Radiation oncology, 2017)
Background: For irradiation treatment planning of meningiomas the use of PET-scans is well established. The most frequently used tracers are either based on amino acids or the somatostatin receptor ligand DOTATOC. Since up to now no inter-institutionally accepted standard PET-tracer has been defined, the aim of this study was to evaluate the influence of these different types of PET-tracers on the GTV-definition. Methods: Twenty-one patients suffering from intracranial meningiomas underwent CT, MRI, FET- and DOTATOC-PET. First, tumour extension was delineated after image-fusion of CT and MRI (GTVCT/MRI). Then distinct GTVs based either on FET- or DOTATOC-PET were contoured and compared with each other as well with GTVCT/MRI. Results: Every tumour showed typical enhancement of DOTATOC, but two meningiomas remained FET-negative. The mean relative overlap volume of GTVFET and GTVDOTATOC was only 41.9% and there was a significantly stronger correlation between GTVCT/MRI and GTVDOTATOC than between GTVCT/MRI and GTVFET. Conclusions: Further investigations are necessary to clarify the minor conformity of DOTATOC- and FET-PET in meningiomas. Because of the receptor targeting, DOTATOC is known to be more specific for meningiomas and will remain the standard in our institution with the known limitation in areas nearby the pituitary gland.